Salivary and crevicular pH as a diagnostic method for periodontal disease - Gutierrez Romero, fabiola (2020)
This review of the literature aims to explain and better understand in a practical and clinical  way  the relationship of salivary Ph and crevicular gingival Ph as an alternative of rapid early diagnosis in patients with chronic periodontitis and gingivitis.The relationship between the progression of periodontal disease and the gingival crevicular fluid is very close, since the development of periodontitis is associated with an increase in the Ph of the gingival crevicular fluid.Saliva has been used in the early detection, risk assessment, diagnosis, prognosis and follow-up of the progression of different oral diseases. The detection of cancer markers such as lung and kidney cancer as well as in infectious and immune diseases.